Commitment Parallax: Paradoxical Theory - Bano, Khushnuma; Ishrat, Azra; Mishra, K.K (International Journal of Psychosocial Rehabilitation, 2020)
Universities are the mainsail in imparting knowledge and shaping the future of a nation and of mankind. Apart from all tangible resources, it is the instructor who ensures this alignment. The commitment of the teaching fraternity towards their institutions is extremely important for imparting quality knowledge and guiding the fresh brains to the next level. This study investigates the difference in teachers’ organizational commitment at government-funded and private universities. Exploratory research design was adapted for the study with a hypothetic deductive approach. Structured questionnaires were administered for conducting personal interviews of 398 teaching staff across various universities in India. A 'R' statistical tool was used to analyze data. The findings from the study were paradoxical to the theoretical establishment of the difference among organizational commitment of teachers employed in government and private universities. There was no sufficient evidence available to establish the causality of organizational commitment with performance. Future studies could be extended to investigate individual performance to establish causality with the organizational commitments considering differences in funding, staffing, and ambience provided by institutes of higher education.